EXPLORING THE EFFECT OF LAISSEZ-FAIRE LEADERSHIP IN PUBLIC SECTOR: A SYSTEMATIC LITERATURE REVIEW - Mohammad, Ariffatri; Abdullah, Zalinawati; Omar, Muhamad Khalil; Ismail, Mohd Khairi (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
This systematic literature review examines the phenomenon of laissez-faire leadership (LFL) in public sector organisations. Given rising demands for innovation, accountability, and reform, the study addresses the critical question of how LFL affects organizational performance and when its use is appropriate. Using the PRISMA 2020 framework, searches were conducted across Scopus and Web of Science (WoS) databases, yielding 40 primary studies that met predefined inclusion criteria. The authors outlined their screening, inclusion, and exclusion criteria in detail to ensure the selection of high-quality empirical studies. The results were classified into three main themes: 1) Laissez-faire leadership and Employee Engagement, 2) Laissez-faire leadership and Employee Performance, and 3) Laissez-faire leadership and Context in Public Sector. Analysis identified substantial variation: in contexts lacking institutional structure, clear governance or active leadership, LFL tends to correlate with poor performance, role ambiguity, and lowered commitment; conversely, within supportive environments featuring stable institutions, participatory frameworks and capable staff, LFL may foster autonomy, creativity, and job satisfaction. These findings suggest that LFL should not be dismissed outright, but rather applied selectively, depending on the organizational culture, stability, and context. Consequently, recommendations urge public sector leaders and policymakers to consider the organizational environment and employee readiness before adopting hands-off leadership approaches.